2020
DOI: 10.1016/j.biopsych.2020.02.309
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-Wide Association Study and Multi-Tissue Replication of Individuals With Alcohol Use Disorder: Evidence for Abnormal Glucocorticoid Signaling Pathway Gene Regulation

Abstract: Alcohol use disorder (AUD) is a chronic debilitating disorder with limited treatment options and poorly defined pathophysiology. There are substantial genetic and epigenetic components; however, the underlying mechanisms contributing to AUD remain largely unknown. We conducted the largest DNA methylation epigenome-wide association study (EWAS) analyses currently available for AUD (total N = 625) and employed a top hit replication (N = 4798) using a cross-tissue/crossphenotypic approach with the goal of identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…We searched major studies of alcohol consumption for all of the genes replicated in three AUD studies 26,42,43 . Heterogenous Nuclear Ribonucleoprotein A1 ( HNRNPA1 ) was significantly hypomethylated in AUD cases in three studies that included saliva, lymphocytes and blood, 29,44,45 and HNRNPA1 methylation was inversely associated with alcohol consumption in blood 42,46 and saliva 26 . HNRNPA1 regulates RNA processing, including transcription, translation, splicing, stability and export.…”
Section: Recent Molecular Discoveriesmentioning
confidence: 99%
“…We searched major studies of alcohol consumption for all of the genes replicated in three AUD studies 26,42,43 . Heterogenous Nuclear Ribonucleoprotein A1 ( HNRNPA1 ) was significantly hypomethylated in AUD cases in three studies that included saliva, lymphocytes and blood, 29,44,45 and HNRNPA1 methylation was inversely associated with alcohol consumption in blood 42,46 and saliva 26 . HNRNPA1 regulates RNA processing, including transcription, translation, splicing, stability and export.…”
Section: Recent Molecular Discoveriesmentioning
confidence: 99%
“…Examining alterations in DNA-methylation in epigenome-wide association studies (EWAS) allows for the investigation of inter-individual differences which are attributable to a phenotype [8]. For example, a recent EWAS of AUD in peripheral blood suggests that networks in glucocorticoid signaling and inflammation-related genes are associated with AUD [9]. Human postmortem brain tissue is a sparse and valuable resource and allows a more direct characterization of AUD mechanisms than possible by analyzing peripheral blood [10].…”
Section: Introductionmentioning
confidence: 99%
“…While a few studies of AUD exist(2-8), they have not yet identified replicating sites across studies. This is likely due to small sample sizes, use of earlier arrays that captured a small number of sites, and inconsistent quality control, data analysis, and interpretation of significant findings (4). The one exception is a study conducted in whole blood that identified several sites associated with AUD across multiple cohorts (4).…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to small sample sizes, use of earlier arrays that captured a small number of sites, and inconsistent quality control, data analysis, and interpretation of significant findings (4). The one exception is a study conducted in whole blood that identified several sites associated with AUD across multiple cohorts (4). In contrast, studies of other alcohol outcomes including consumption and phosphatidylethanol, a metabolite of ethanol, have identified 7 sites that replicate across studies (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation